Ancestral ecological regime shapes reaction to food limitation in the Least Killifish, Heterandria formosa. Issue 11 (6th April 2021) - Felmy, Anja; Leips, Jeff; Travis, Joseph
Abstract: Populations with different densities often show genetically based differences in life histories. The divergent life histories could be driven by several agents of selection, one of which is variation in per‐capita food levels. Its relationship with population density is complex, as it depends on overall food availability, individual metabolic demand, and food‐independent factors potentially affecting density, such as predation intensity. Here, we present a case study of two populations of a small live‐bearing freshwater fish, one characterized by high density, low predation risk, low overall food availability, and presumably low per‐capita food levels, and the other by low density, high predation risk, high overall food availability, and presumably high per‐capita food levels. Using a laboratory experiment, we examined whether fish from these populations respond differently to food limitation, and whether size at birth, a key trait with respect to density variation in this species, is associated with any such differential responses. While at the lower food level growth was slower, body size smaller, maturation delayed, and survival reduced in both populations, these fitness costs were smaller in fish from the high‐density population. At low food, only 15% of high‐density fish died, compared to 75% of low‐density fish. This difference was much smaller at high food (0% vs. 15% mortality). The increased survival of high‐density fish may, at least partly, be due to their larger size at birth. Moreover, being larger at birth enabled fish to mature relatively early even at the lower food level. We demonstrate that sensitivities to food limitation differ between study populations, consistent with selection for a greater ability to tolerate low per‐capita food availability in the high‐density population. While we cannot preclude other agents of selection from operating in these populations simultaneously, our results suggest that variation in per‐capita food levels is one of those agents. Abstract : When populations with contrasting densities have different life histories, one of the agents of selection driving these differences might be variation in per‐capita food levels. We conducted a laboratory experiment to test whether two populations of the Least Killifish, one experiencing a higher and one a lower population density, respond differently to food limitation. As expected if high‐density fish were adapted to food scarcity, we found that they survived significantly better at the lower food level than low‐density fish, suggesting that variation in per‐capita food availability is one of the selective agents that operate in these populations.